Activity of Oligoresveratrols from Stem Bark of Hopea mengarawan (Dipterocarpaceae) as Hydroxyl Radical Scavenger - SRI ATUN (HAYATI Journal of Biosciences, 2006)
Four oligoresveratrols ranging from dimer to tetramer, isolated from stem bark of Hopea mengarawan (Dipterocarpaceae) plants were tested for their activity as hydroxyl radical scavenger. The activity of these compounds was evaluated against the 2-deoxyribose degradation induced by the hydroxyl radical generated via a Fenton-type reaction. Result showed that balanocarpol, heimiol A, vaticanol G, and vaticanol B had IC50 3.83; 15.44; 2.01; and 4.71 uM, respectively. These results suggest that oligoresveratrols from stem bark of H. mengarawan maybe useful as potential sources of natural antioxidants. Key words: Oligoresveratrol, Hopea mengarawan